(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
River sand mining has become a widespread practice to meet construction material needs. However, this activity often ignores significant environmental impacts, resulting in damage to river ecosystems and the surrounding area. This study aims to further explore the environmental damage caused by sand mining activities along rivers. Using qualitative research methods and a literature review approach, data was obtained from various academic sources such as journals, books, research reports, and other relevant publications. Data analysis was conducted through identification, categorization, and interpretation of information to understand damage patterns, causal factors, and the resulting ecological and social consequences. The results indicate that unregulated sand extraction results in river morphological degradation, reduced air quality, loss of aquatic habitat, increased riverbank erosion, and changes in airflow patterns. Furthermore, social impacts such as land conflicts and reduced livelihoods of local communities are also common. This study emphasizes the implementation of strict regulations, effective oversight, and the implementation of responsible mining practices to minimize negative impacts on the environment and river ecosystems.